Research and development of a pilot project using GNSS and Earth observation (GeoSHM) for structural health monitoring of the Forth Road Bridge in Scotland - Meng, Xiaolin; Xie, Yilin; Bhatia, Paul; Sowter, Andrew; Psimoulis, Panos; Colford, Barry; Ye, Jun; Skicko, Mike; Dimauro, Marco; Ge, Maorong; Li, Xingxing (2016)
GeoSHM (GNSS and Earth Observation for Structural Health Monitoring) is a feasibility study project funded under the Integrated Application Promotion (IAP) program of the European Space Agency (ESA) in August 2013. Through integrated use of GNSS, Remote Sensing technologies and environmental data, GeoSHM can offer bridge owners an effective tool to assess the operational conditions of their assets. A reference system that consists of four GNSS receivers and two anemometers was installed on the Forth Road Bridge (FRB) in Scotland. This first stage monitoring system is producing precise 3D real-time displacements under different loading conditions. It can also provide essential land movement information to assess potential threats due to underground water extraction, geo-hazards and other industrial activities. The GeoSHM Feasibility Study has proved that even a small scale monitoring system can make possible for the Bridgemaster of the FRB to fully understand the loading and response effect of the bridge, and identify unusual deformations under extreme weather conditions (wind gust, etc.). Furthermore, EO data has proved to be extremely useful for the subsidence detection, as the SAR interferometry images have shown that there is no significant subsidence of the towers of the FRB or in the surrounding area. Gathering real-time GNSS data has produced continuous and accurate estimation of the displacement time-series of the structure. The issues and gaps identified from GeoSHM FS will form a solid foundation for the next stage development of GeoSHM service – demonstration, which is a two-year project and have started in February 2016. A new consortium of GeoSHM has been formed, focusing on significant refinements to the system reliability, sensor integration, data acquisition, data transmission, data fusion and SHM information extraction. This further developed GeoSHM system will be installed on a few Chinese bridges and the reference monitoring system on the FRB will be expanded as a pre-operational system.